Representações das relações entre cristãos e não-cristãos na Chanson de Roland e em Fierabras durante a monarquia capetíngia do Século XII - MORAIS, Elisângela Coelho (2023)
The research presented here seeks to analyze how discursive representations were constructed about the relationship between Christians and non-Christians during the Capetingian monarchy in France in the 12th century, as well as how its consolidation took place in the social imagination of the time. gesture: La Chanson de Roland, in two versions, one written between the end of the 11th century and the beginning of the 12th century, contained in the Oxford Manuscript, and another version, from the second quarter of the 12th century, written in the Châteauroux Manuscript. The other gesture used is the text contemporary to Châteauxoux, called Fierabras, where we see the same characters from the Chanson de Roland, involved in the clash against the Saracens, led by Fierabras, from Alexandria and his father, al mirant Balan, after they had sacked the city of Rome and taken the relics of the Passion of Christ. Analyzing these writings, using the concepts of representation and otherness, we understand the impressions of Christians on Islamists and the views they have on Christians, as well as the repercussions arising from this encounter. Just like the analysis from a decolonial point of view, we find strong evidence of these narratives beyond the Atlantic, in Brazilian territory under various cultural and religious manifestations.